Advances in multimedia information processing - PCM 2016 : 17th Pacific-Rim Conference on Multimedia, Xi'an, China, September 15-16, 2016, proceedings, Part I /: 17th Pacific-Rim Conference on Multimedia, Xi'an, China, September 15-16, 2016, proceedings, Part I. (2016) - Unknown
No abstract available